Implementasi Model Pembelajaran Problem Based Learning Berbantuan Media Zep Quiz terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas VII SMP - Aldila Dewi Ratna Supriadi; Masitah; Sonja Verra Tinneke Lumowa; Nelda Anasthasia Serena; Sri Purwati (UNIB Press, 2026)
The student achievement in science is characterized by low levels of student engagement, students’ lack of mastery of basic material, and the lack of implementation of media-assisted Problem-Based Learning (PBL) in the learning process. These conditions prompted this study, which aims to examine the implementation of media-assisted PBL using the Zep Quiz on student achievement in science for seventh-grade students at SMP Negeri 4 Samarinda. This study employed a quantitative approach using a quasi-experimental design with a pretest-posttest nonequivalent control group design. Sampling was conducted using purposive sampling, with a total sample of 54 students comprising Class VII-6 as the control group and Class VII-7 as the experimental group. In the experimental class, the Problem-Based Learning model supported by the Zep Quiz media was implemented during the introductory activities as well as during the stages of analyzing and evaluating the problem-solving process. Data analysis was conducted using the N-Gain test and the independent samples t-test. The analysis results showed that the average N-Gain scores in the control and experimental classes were in the moderate category, with values of 0,45 and 0,60, respectively. The results of the independent samples t-test yielded a significance value of 0,000 < 0,05, so H0 was rejected and Ha was accepted. Based on the research results, it can be concluded that the implementation of the Problem-Based Learning model supported by the Zep Quiz media has an effect on student learning outcomes in 7th-grade science at SMP Negeri 4 Samarinda.